Restoring a Javanese Inscription to its Proper Place: The Minto Stone (Sangguran Charter) Seen in New Light. - Griffiths, Arlo; Sastrawan, Wayan Jarrah; Eko Bastiawan (Journal of the Humanities & Social Sciences of Southeast Asia & Oceania / Bijdragen tot de Taal-, Land- en Volkenkunde, 2024)
More than most other stone inscriptions from pre-Islamic Java, the Minto stone (Sangguran charter) has broad name recognition in Indonesia today. The story of the stone's removal, more than two hundred years ago during the British occupation of Java, from its original setting in the mountainous area north-west of Malang to its current location at the Minto Estate in the Scottish Borders, has stimulated popular imagination. Given the ever-increasing global relevance of the issue of the repatriation of heritage items to their countries of origin, this prestigious stone stele has become the object of significant media attention and is one of the highest priorities among the artefacts which the Indonesian government hopes to bring home. Compared with how much public attention is given to the issue of where the stone belongs, very little attention has been paid to the textual content of the charter engraved on it. In these pages, we attempt to recentre attention on the inscription as a document of intrinsic historical interest. To this end, we first investigate the provenance of the stone. We then review its heritage status, drawing attention to its significance for the local community. Our focus, however, is on the philological study of the inscribed text, of which we present—for the first time—a complete version. This version is based on direct inspection and high-resolution images of the stone, accompanied by an integral translation reflecting the state of scholarly understanding of Old Javanese epigraphy. The epigraphic core of this study is then followed by a discussion of some of the historical implications of the text. Among the topics we review are the chronology and nature of the shifting of political power from Central to East Java in the tenth century CE as well as the culinary and material aspects of communal feasts in that period.